2013
DOI: 10.1007/s11524-013-9849-0
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Effects of Adolescent Smoking on Depression and Socioeconomic Status in Adulthood in an Urban African American Cohort

Abstract: Despite known adverse causal effects of cigarette smoking on mental health, findings for the effects of adolescent cigarette smoking on later depression and socioeconomic status remain inconclusive. Previous studies have had shorter followup periods and did not have a representative portion of the African American population. Using an analytical method that matches adolescent smokers with nonsmokers on childhood and background variables, this study aims to provide evidence on the effects of adolescent regular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 68 publications
0
7
0
Order By: Relevance
“…Data from the National Longitudinal Study of Adolescent Health indicate that, after adjusting for age and race, men who had no further education and were economically inactive had four times greater odds of heavy smoking than men with further education (Yang et al, 2008). We also previously demonstrated the association of adolescent smoking on later educational attainment with the same study sample as this paper using a propensity score matching method (Strong, Juon, & Ensminger, 2014). On the other hand, educational attainment was found to be associated with the use of alcohol (Melotti et al, 2011), marijuana (Grant et al, 2012), and other drugs (Fothergill et al, 2008).…”
Section: Introductionmentioning
confidence: 72%
See 2 more Smart Citations
“…Data from the National Longitudinal Study of Adolescent Health indicate that, after adjusting for age and race, men who had no further education and were economically inactive had four times greater odds of heavy smoking than men with further education (Yang et al, 2008). We also previously demonstrated the association of adolescent smoking on later educational attainment with the same study sample as this paper using a propensity score matching method (Strong, Juon, & Ensminger, 2014). On the other hand, educational attainment was found to be associated with the use of alcohol (Melotti et al, 2011), marijuana (Grant et al, 2012), and other drugs (Fothergill et al, 2008).…”
Section: Introductionmentioning
confidence: 72%
“…At that time, it was composed of 99% African Americans and 51.2% females (Kellam, Branch, Agrawal, & Ensminger, 1975). More detail on attrition analyses can be found in our previous publication (Strong et al, 2014). …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, there are some contradicting results. Studies conducted with African Americans failed to find any harmful physical effects of cigarette smoking on major adulthood depressive disorders [ 44 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Exposure to high levels of nicotine during adolescence may result in damage to sensitive developmental phases and may have a cumulative effect over time. Strong et al [ 8 ] showed, that early cigarette smoking among African Americans is correlated with later educational problems and long-term unemployment. Daily smoking increases the likelihood of remaining or becoming physically inactive over time [ 9 ].…”
Section: Introductionmentioning
confidence: 99%